PROFIL PASIEN ENDOSKOPI GASTROINTESTINAL DI RSUP DR. M. DJAMIL PADANG TAHUN 2022 - Alifssa Rihhadatul Aisy; Aryaldy Zulkarnaini (Yayasan Nusantara Hasana Berdikari, 2023)
Technological developments have a positive impact on medicine, especially in the diagnosis of disease. One example is the use of endoscopic tools as a useful supporting examination to identify abnormalities in the organs of the human body. Gastrointestinal endoscopic examination is a technique in gastroenterology - hepatology which consists of Esophago Gastro Duodenoscopy (EGD) and colonoscopy. The initial indication for endoscopic examination is generally dyspepsia, the high incidence of dyspeptic syndrome, endoscopic examination is used to confirm the diagnosis and several definite diagnoses are obtained such as los angeles grade A classification esophagitis, erosive gastritis, and duodenitis. This study aims to determine the profile of gastrointestinal endoscopy patients at Dr. M. Djamil Padang Hospital in 2022. This type of research is categorical descriptive research, using a cross sectional research design. Sampling was done with total sampling technique. The largest age group was 56 - 65 years 196 patients (23.2%) with male gender 430 patients (50.9%). The most common endoscopic examination action was EGD 646 patients (76.5%). The most common indication for EGD examination was dyspepsia syndrome 228 patients (35.3%), while for colonoscopy examination the most common indication was Susp. Inflammatory Bowel Disease as many as 49 patients (24.7%). The most common endoscopic examination results in EGD actions were chronic gastritis (antrum) as many as 81 patients (9.6%) while in colonoscopy actions were grade II internal hemorrhoids as many as 29 patients (14.6%). The largest age group was 56 - 65 years, with male gender with EGD examination, and the most indications for EGD were dyspepsia syndrome, while colonoscopy was Susp. Inflammatory Bowel Disease, with the most examination results for EGD was chronic gastritis (antrum) and for colonoscopy was grade II internal hemorrhoids.